PERBEDAAN MOTIVASI KERJA ANTARA KARYAWAN KONTRAK DAN KARYAWAN TETAP PADA PT. BANK RAKYAT INDONESIA CABANG CIMAHI - Fajar Purnama Arif (Psympathic : Jurnal Ilmiah Psikologi, 2012)
This research used comparative study to compare motivation between contracted employee and permanent employee who work at PT Bank Rakyat Indonesia Cimahi branch. Sample are 40  employee represent teller and customer service division. Qualitative study is used with comparative analysis. Instrument used is Motivation Assesment Inventory from Denies C Kinlaw (1981. Data analysis result probalility more than 0,5 so that Ho  is accepted and H1  is rejected. It is concluded that there is different work motivation between contracted employee and permanent employee.